The Effects of Cities’ Membership in the Cittaslow Network in the Opinion of their Residents: the Example of Barczewo and Biskupiec - Wierzbicka, Wioletta; Mociun, Katarzyna (Olsztyn Economic Journal, 2024)
The aim of the research was to assess the effects of cities’ membership in the Polish National Cittaslow Network based on the opinions of their residents. An attempt was made to identify both positive and negative effects felt in cities and to determine in which areas they occur most. The study used the survey research method. The survey questionnaire was addressed to residents of two slow cities: Biskupiec and Barczewo. Most respondents indicated positive effects of membership in the Cittaslow network. The most benefits were indicated in three areas of the city’s functioning: increased tourist attractiveness, expanded cultural offer of the city and better promotion of the city. Importantly, the majority of respondents support the city’s continued membership in the network and believe that it will accelerate the economic growth rate and the city’s long-term development.